Peningkatan Keterampilan Menulis Teks Persuasi Siswa Menggunakan Model Pembelajaran Project Based Learning (PJBL) Kelas VIII E SMPN 1 Geneng - Khoirul Anwar; Wiwik Sri Handayani; Eni Winarsih (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
This research aims to solve the problem of low student writing skills. Through the Project Based Learning model, it is expected to be able to improve students' writing skills, especially in Indonesian language subjects on persuasion text material. This research is included in the type of Classroom Action Research (PTK) using the model of Kemmis and Mc. Taggart model. The subjects of this study were 31 students of class VIII E SMPN 1 Geneng, Ngawi. The approach in this study used qualitative descriptions. While the data collection techniques used test and non-test instruments in the form of observation sheets. Analysis of data for each cycle obtained test results that in cycle 1 student completeness only reached 6.45% (not yet achieved) then in the improvement in cycle 2 it increased to 16.12% (has been achieved). In addition, the non-test results showed that the effectiveness of using the Project Based Lerning learning model in cycle 1 was 90.32% (less) and increased in cycle 2 to 90% (very good).